Existence of weak solutions for a class of systems semilinear elliptics - Tineo Condeña, Marlon Yvan (2018)
This article summarizes the main contributions of the thesis with the title "Existence of solutions for a class of semilinear elliptical systems". This thesis focuses on a didactic exhibition of the article published by Afrouzi, G., Mirzapour, A. and Zographopoulos, N.[1], whose objective is to prove the existence of weak solutions to a class of semilinear potential elliptic systems of the formwhere the domain Ω is a bounded domain in ℝN (N > 2), regular border, the weights a(x), b(x) are measurable nonnegative weights on Ω, (Fu, Fv) = ∇F stands for the gradient of F in the variables (u; v) ∈ ℝ2 and λ is a positive parameter.